Jaya: An Illustrated Retelling of the Mahabharata - Devdutt Pattanaik (India Penguin Books, 2010)
School of Arts, Humanities and Social Science
MIR No: 153
Order Date: 2024-07-08
Order No: 406-1119758-4239515
Received Date: 2024-08-27
Keywords: Mahabharata, Religion